2020
DOI: 10.1101/2020.09.17.301168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Applying Machine Learning Technology in the Prediction of Crop Infestation with Cotton Leafworm in Greenhouse

Abstract: The use of technology in agriculture has grown in recent years with the era of data analytics affecting every industry. The main challenge in using technology in agriculture is identification of effectiveness of big data analytics algorithms and their application methods. Pest management is one of the most important problems facing farmers. The cotton leafworm, Spodoptera littoralis (Boisd.) (CLW) is one of the major polyphagous key pests attacking plants includes 73 species recorded at Egypt. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…They before shipped the dossier to a machine-education invention to produce a warning meaning before effecting both the dossier and the warning communication by way of a graphical user interface (GUI). Several machine learning techniques have been built by Tageldin et al [ 8 ] to predict plant infestation with CLW. The current research established a framework for machine learning to forecast CLW infestation in greenhouse plants.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They before shipped the dossier to a machine-education invention to produce a warning meaning before effecting both the dossier and the warning communication by way of a graphical user interface (GUI). Several machine learning techniques have been built by Tageldin et al [ 8 ] to predict plant infestation with CLW. The current research established a framework for machine learning to forecast CLW infestation in greenhouse plants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, environmental sensing parameters such as greenhouse gases, temperature, soil moisture, and light must all be maintained and monitored. This issue could be solved by implementing an Internet of Things (IoT) innovation in intelligent agriculture, which entails the precise application of certain greenhouse factors for optimal plant development, such as temperature management, water flow control, and light radiation, among other things [ 8 , 9 ]. The main contributions of the paper are as follows.…”
Section: Introductionmentioning
confidence: 99%
“…While rainfall had a significant and opposite impact, temperature strongly and positively correlated with the frequency of leafhoppers and whiteflies. The genotypes were utterly identical to one another [29]. The evolutionary history and ecological ramifications of the Bemisia tabaci complex have been studied in Ecuador.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, this algorithm can improve the generalization ability of the model, thereby providing new ideas and methods for the detection and prediction of crop diseases [22]. Ahmed et al [23] used the XGBoost algorithm to predict the occurrence of vegetation infestation by cotton leaf miner with a prediction accuracy of 84%, which was higher than the prediction results obtained by algorithms such as RF and logistic regression. Sandino et al [24] identified healthy and infested trees in forests by exotic pathogens through the XGBoost algorithm with a classification accuracy of 97%.…”
Section: Introductionmentioning
confidence: 99%